Molecular characterization of bacterial microbiota associated with infectious bovine keratoconjunctivitis in Michoacán, Mexico - Ríos-Alanís, Ana M.; López-Meza, Joel E.; Ochoa-Zarzosa, Alejandra; Segura-Correa, Jose C.; Herrera-Camacho, José (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: The most common ocular disease affecting cattle worldwide is infectious bovine keratoconjunctivitis (IBK), which has been associated with Moraxella bovis bacterium. Objective: To report the molecular characterization of the ocular bacterial microbiota and its relation to IBK in cattle in two dairy regions in Michoacán, Mexico. Methods: A total population of 761 bovines were evaluated, of which 17 (2.23%) showed symptoms of IBK. Thirty-eight bacterial isolates from ocular samples of bovines with IBK were characterized by Gram-staining and antimicrobial sensitivity. In addition, isolates were identified by sequence comparisons of the 16S ribosomal gene. Results: The genus Moraxella was one of the most abundant bacteria and M. bovoculi was the most predominant species. Conclusion: The bacterial isolates identified in eye lesions of cattle and associated to IBK are diverse. To the author´s knowledge, this is the first study on the subject in Mexico; therefore, more research is needed to estimate the incidence of IBK and determine its associated microbiota.